ISLAM'S CONTRIBUTION TO THE DEVELOPMENT OF ISLAMIC EDUCATION IN THE ERA OF INDUSTRY 4.0 - Wastuti Wastuti; Zamroni Zamroni; Tahir Tahir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The Industry 4.0 era has brought fundamental changes to various aspects of life, including Islamic education. This article aims to analyze Islam's contribution to this digital era through three main dimensions: philosophical, historical, and practical, and its implications for the development of Islamic education. The study used a Systematic Literature Review (SLR) approach to scientific publications from 2020–2025. The results show that Islam plays a strategic role as a moral, epistemological, and applicative foundation capable of balancing technological progress with spiritual values. In the philosophical dimension, Islam provides an ethical foundation and the value of monotheism to ensure technology is used humanely and brings benefits to all humanity. In the historical dimension, Islamic education demonstrates high adaptability to changing times. In the practical dimension, Islamic educational institutions have begun implementing innovations such as blended learning, digital literacy, and artificial intelligence (AI). Thus, Islam contributes to shaping character-based, competitive, and spiritually oriented education in the Industry 4.0 era.